ANALISIS KEWENANGAN BAWASLU KABUPATEN/KOTA DALAM PENYELESAIAN SENGKETA PROSES PEMILIHAN UMUM BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - Melia Surya Dharma; Syamsir Syamsir; Bustanuddin Bustanuddin (Universitas Jambi, Fakultas Hukum, 2022)
Abstract Based on Article 99 of Law Number 7 of 2017 concerning General Elections that the authority of Bawaslu is to receive and follow up on reports relating to alleged violations of the implementation of laws and regulations governing elections, examine and review election violations in the province and recommend the results of the examination and review of parties regulated by law. Dispute resolution is a process, method or act of resolving something that causes differences of opinion, disputes or quarrels. Every dispute, whatever happens, always demands a solution and resolution. Based on Law Number 7 of 2017 concerning General Elections, Article 469 Paragraph (1) states that the Bawaslu decision regarding disputes over the General Election process is a final and binding decision. General Election, hereinafter referred to as General Election, is a means of people's sovereignty to elect members of the People's Representative Council, members of the Regional Representatives Council, President and Vice President, and to elect members of the Regional People's Representative Council, which are carried out directly, publicly, freely, confidentially, honestly and fairly. within the unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Keywords: Authority, Bawaslu, Dispute Resolution, Election Abstrak Berdasarkan Pasal 99 Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum bahwa kewenangan bawaslu dengan menerima dan menindak lanjuti laporan yang berkaitan dengan dugaan pelanggaran terhadap pelaksanaan peraturan perundang-undangan yang mengatur tentang pemilu, memeriksa dan mengkaji pelanggaran pemilu diwilayah provinsi serta merekomendasikan hasil pemeriksaan dan pengkajian kepada pihak yang diatur dalam undang-undang. Penyelesaian sengketa adalah proses, cara atau perbuatan dalam menyelesaikan sesuatu yang menyebabkan perbedaan pendapat, perselisihan atau pertengkaran. Setiap sengketa apapun yang terjadi, selalu menuntut pemecahan dan penyelesian. Berdasarkan Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan umum Pasal 469 Ayat (1) Menyebutkan bahwa putusan Bawaslu mengenai sengketa proses Pemilihan Umum merupakan keputusan yang bersifat final dan menginkat. Pemilihan Umum yang selanjutnya disebut Pemilu adalah sarana kedaulatan rakyat untuk memilih anggota Dewan Perwakilan Rakyat, anggota Dewan Perwakilan Daerah, Presiden dan Wakil Presiden, dan untuk memilih anggota Dewan Perwakilan Rakyat Daerah, yang dilaksanakan secara langsung, umum, bebas, rahasia, jujur dan adil dalam Negara kesatuan Republik Indonesia berdasarkan Pancasila dan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Kata kunci: Kewenangan, Bawaslu, Penyelesaian Sengketa, Pemilu